Foundations of Information and Knowledge Systems 8th International Symposium, FoIKS 2014, Bordeaux, France, March 3-7, 2014. Proceedings - Beierle, Christoph; Meghini, Carlo (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the proceedings of the 8th International Symposium on Foundations of Information and Knowledge Systems, FoIKS 2014, held in Bordeaux, France, in March 2014. The 14 revised full papers presented together with 5 revised short papers and two invited talks were carefully reviewed and selected from 52 submissions. The papers address various topics such as database design, dynamics of information, information fusion, integrity and constraint management, intelligent agents, knowledge discovery and information retrieval, knowledge representation, reasoning and planning, logics in databases and AI, mathematical foundations, security in information and knowledge Systems, semi-structured data and XML, social computing, the semantic Web and knowledge management, as well as the WWW.